The Influence of The Work Environment, Company Culture on The Retention Rate of Employees of PT. PG Rajawali II - Aulia, Lingga Afrilla; Fasha, Aprillia Wulan Da; Syahroni, Bachrudin; Mahadianto, Moh Yudi (Journal Research of Social Science, Economics, and Management, 2025)
This research aims to examine the influence of the work environment and company culture on the retention rate of employees at PT. PG Rajawali II Cirebon. Employee retention is one of the important aspects of human resource management because it directly affects the stability of the organization and the company's operations. This researcher uses a quantitative approach using the Menetode Partial Least Square. Collecting data using a questionnaire of 60 employees of PT. PG Rajawali II Cirebon. The results show that the work environment has an influence on employee retention. It indicates that if PT. PG Rajawali II Cirebon has comfortable working conditions, so employees are more loyal to the company. Company culture also has a significant influence on employee retention. These findings show that companies must strengthen their work environment and company culture in order to improve employee retention and reduce employee turnover rates.